The generic structures and lexico-grammaticality in English academic research papers. Issue 2 (3rd April 2017) - Valipour, Valeh; Assadi, Nader; Asl, Haniyeh Davatgari
Abstract: The present study aimed to discover how selected English language authors employ specific rhetorical, grammatical, and stylistic elements in presenting new knowledge to the target audience and how they communicate science to the community of academicians in order to convey scientific information to various audiences. To this end, the generic structures, as well as lexico-grammaticality systems inbuilt in introduction sections of English academic research papers of three different disciplines, linguistics, chemistry and software engineering, were explored. To collect the data, a corpus consisting of 90 papers, 30 for each discipline, published between 2014 and 2016 in Elsevier journals was selected randomly. For genre analysis, Hasan's model of generic structure potential was used, while Halliday's model was used for the analysis of lexico-grammaticality systems. The results showed that 'Previous study' and 'Purpose of study' were the obligatory elements among the 11 types of generic structures. Furthermore, material process, declarative mood, the use of conjunctions in textual theme and circumstantial adjunct were mostly used, while no interpersonal theme was found in the obligatory elements. The findings promise pedagogical implications for novice writers and university students of English language generally, and second language or foreign language writers from different cultures in different fields of study, in particular.